2013
DOI: 10.1007/s00429-013-0564-0
|View full text |Cite
|
Sign up to set email alerts
|

Gray matter density in relation to different facets of verbal creativity

Abstract: Neuroscience studies on creativity have revealed highly variegated findings that often seem to be inconsistent. As recently argued in Fink and Benedek (Neurosci Biobehav Rev, 2012), this might be primarily due to the broad diversity in defining and measuring creativity as well as to the diversity of experimental procedures and methodologies used in this field of research. In specifically focusing on one measure of brain activation and on the well-established process of creative ideation (i.e., divergent thinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 29 publications
8
66
0
Order By: Relevance
“…Effects were considered to be significant when the volume of a cluster was greater than the minimum cluster size on whole brain GMV (determined using the Monte Carlo simulation; 1032 mm 3 ), in which case the probability of a type I error was less than 0.01. Generally, AlphaSim has been widely used in previous VBM studies (DeYoung et al, 2010;Fink et al, 2013;Kong et al, 2013;Leung et al, 2013;W. Li et al, 2014;Schwartz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Effects were considered to be significant when the volume of a cluster was greater than the minimum cluster size on whole brain GMV (determined using the Monte Carlo simulation; 1032 mm 3 ), in which case the probability of a type I error was less than 0.01. Generally, AlphaSim has been widely used in previous VBM studies (DeYoung et al, 2010;Fink et al, 2013;Kong et al, 2013;Leung et al, 2013;W. Li et al, 2014;Schwartz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, however, a more consistent picture of the creative brain has begun to emerge (Beaty et al, 2014;Fink et al, 2013;Jauk et al, 2015;Kühn et al, 2014;Takeuchi et al, 2012). For instance, a recent voxel-based morphometry study investigating verbal creative potential reported positive associations between indicators of creativity and brain structure in the precuneus (Fink et al, 2013). A subsequent study by Emanuel Jauk and colleagues (2015) also found a relationship between ideational originality and grey matter volume in the precuneus.…”
Section: Introductionmentioning
confidence: 93%
“…Although structural imaging research has revealed individual differences in creative potential or performance (Chen et al, 2014;Fink et al, 2013;Jung et al, 2010;Takeuchi et al, 2010;Zhu et al, 2013), such findings are not universal, possibly due to a diversity of designs and methodologies employed (Dietrich and Kanso, 2010;Fink et al, 2013). More recently, however, a more consistent picture of the creative brain has begun to emerge (Beaty et al, 2014;Fink et al, 2013;Jauk et al, 2015;Kühn et al, 2014;Takeuchi et al, 2012). For instance, a recent voxel-based morphometry study investigating verbal creative potential reported positive associations between indicators of creativity and brain structure in the precuneus (Fink et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, other studies of resting state paradigms have revealed that resting state brain activity involving the DMN is important for creativity measured by divergent thinking (Takeuchi et al, 2012a;Wei et al, 2013). Some structural studies have indicated that the brain structure of the key nodes of the DMN is associated with creativity (Fink et al, 2013). In addition, DMN is thought to be critically involved in self-referential or introspective cognitive activities, such as those involving autobiographical memory, and social cognition, such as the theory of mind (Buckner et al, 2008;Fair et al, 2008;Schilbach et al, 2008).…”
Section: Included Gray Matter Areasmentioning
confidence: 98%